P39 Longitudinal changes of cerebral white matter tissue microstructure in early-onset systemic lupus erythematosus. (23rd March 2020) - Silvagni, Ettore; Inglese, Francesca; Bortoluzzi, Alessandra; Revenaz, Alfredo; Borrelli, Massimo; Steup-Beekman, Margreet; Huizinga, Tom; Bresser, Jeroen De; Ronen, Itamar; Fainardi, Enrico; Govoni, Marcello; Ercan, Ece
Abstract : Background: Diffusion tensor imaging (DTI) studies revealed alterations of cerebral white matter (WM) tissue microstructure in patients with established Systemic Lupus Erythematosus (SLE), highlighting longitudinal changes in DTI metrics. The main aim of this study was to evaluate longitudinal variations of DTI metrics in different WM tracts of newly-diagnosed SLE patients. Methods: In a prospective single-centre observational study (2013–2018), patients meeting revised ACR or SLICC classification criteria, aged less than 55, within 24 months from diagnosis, were evaluated with brain MRI (1.5T Philips Achieva) at baseline (T0) and after at least 12 months (FU). DTI data (15 directions, b-value 800s/mm 2 ) were analysed using ExploreDTI software. Automatic lesion segmentation was performed using Lesion Prediction Algorithm (Matlab16). An in-house developed semi-automated WM tracts segmentation algorithm was used to assess fractional anisotropy (FA), mean (MD), radial (RD), axial diffusivity (AD) values in different normal-appearing WM tracts. Variations in neuroimaging data were analysed by Wilcoxon matched-pairs signed-ranks test. Results: 17 early SLE patients were included. After mean 456.3(87.1) days, mean(SD) FA values significantly decreased at left corticospinal tract (T0: 0.483(0.032); FU: 0.470(0.034), p=0.0040) and posterior limb of left internal capsule (0.590(0.020) vs 0.580(0.024), p=0.0396), with increase in MD (0.755 vs 0.770, p=0.0023) and RD values (0.467 vs 0.482, p=0.0019) (figure 1 ). Increase in MD and RD values was independent of baseline neurologic symptoms, disease activity and comorbidities. Conclusions: Longitudinal decrease in FA and increase in MD start in early phases of SLE course, even in absence of overt NP symptoms, reflecting a compromised WM tissue microstructure.